APLIKASI MESIN SPINNER BERKECEPATAN RENDAH UNTUK MENURUNKAN KADAR AIR DAN MINYAK KERIPIK IKAN UKURAN BESAR DI UKM BERKAH - Rianingsih, Laras; Amalia, Ulfah; Wijayanti, Ima; Suharto, Slamet (Universitas Sebelas Maret (UNS), 2018)
Rawa pening is a water area located in the Banyubiru area of Semarang Regency. Aside from being usedas a place for fish farming, the area around Rawa Pening is used as a tourist spot for example “Bukit Cinta”.Around the location it will be easy to find entrepreneurs who provide souvenirs typical of these tourist locations.The typical Bukit Cinta souvenirs is a variety of chips, including fish chips. There are 2 fish chips in Bukit Cinta,small size chips and large size chips. The problem was the shelf life of large size chips is short because theycannot be spinered so that the oil content is still high and than pronoun to oxidation. Low speed spiner tools canbe a solution to overcome existing problems. The results of the spinner machine application are obtained lowermoisture content and lipid content than products without being spinnered. Moisture content after the spinningprocess using spiner machine, the wader chips was 3.25% and tilapia chips were 3.97%. While the wader chipslipid content was 31.16% (bk) and tilapia chips 3.97% (db).